Insights on carbapenem-resistant Pseudomonas aeruginosa: phenotypic characterization of relevant isolates - Gajdács, Márió; Kárpáti, Krisztina; Stájer, Anette; Zanetti, Stefania; Donadu, Matthew Gavino (Acta Biologica Szegediensis, 2021)
Pseudomonas aeruginosa (P. aeruginosa) is ubiquitous in nature, and may be a causative agent in severe, life-threatening infections. In >60% of cases, β-lactam antibiotics are used in the therapy of P. aeruginosa infections, therefore the emergence of carbapenem-resistant P. aeruginosa (CRPA) is a signiﬁcant clinical concern. In this study, phenotypic methods were used to characterize ﬁfty-four (n = 54) P. aeruginosa isolates, which were included based on their suspected non-susceptibility to meropenem. Minimum inhibitory concentrations (MICs) of meropenem, ceftazidime, cefepime, ciprofloxacin, gentamicin, were determined using E-tests, while colistin MICs were determined using broth microdilution. The isolates were subjected to the modiﬁed Hodge test (MHT), the modiﬁed carbapenem-inactivation method (mCIM) and the imipenem/EDTA combined disk test (CDT). AmpC and eﬄux pump overexpression was studied using agar plates containing cloxacillin and phenylalanine-arginine β-naphthylamide (PAβN), respectively. Assessment of bioﬁlm-formation was carried out using the crystal violet tube-adherence method. 38.9% of the strains showed meropenem MICs in the resistant range (>8 mg/L). Eﬄux-pump overexpression and AmpC-hyperproduction was seen in 44.4% and 35.2% of isolates, respectively. 88.8% of the isolates were characterized as strong bioﬁlm-producers. On the other hand, the presence of carbapenemases was suspected in a minority (16.7%) of tested isolates. As safe and eﬀective therapeutic options in carbapenem-resistant Gram-negative infections are severely limited, characterization of these isolates using phenotypic and molecular-based methods is important to provide insights into the epidemiological features of these pathogens.